2014
DOI: 10.3897/zookeys.381.6445
|View full text |Cite
|
Sign up to set email alerts
|

A cornucopia of cryptic species - a DNA barcode analysis of the gobiid fish genus Trimma (Percomorpha, Gobiiformes)

Abstract: A genetic analysis of partial mitochondrial 5’ cytochrome c oxidase I gene (DNA barcode) sequences of 473 specimens assigned to 52 morphological species (including four known, but not formally named, species) of the gobiid genus Trimma revealed the presence of 94 genetic lineages. Each lineage was separated by > 2% sequence divergence. Thus there were an additional 42 haplogroups recognizable as provisional candidate species given that a value of > 2% difference is typical of different species of fishes. Such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 18 publications
3
46
0
Order By: Relevance
“…An extensive DNA barcode study on Microgastrinae wasps demonstrated significant insights into their taxonomy and species discovery [22]. Such cryptic diversity has been uncovered using DNA barcodes in other animal taxa, including crustaceans, diatoms, and fish [23][24][25]. The use of DNA barcodes for the discovery of new species is emerging as a powerful tool to clarify species boundaries and to quantify species diversity [26].…”
Section: Box 1 Building the Dna Barcode Library Using Sanger Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…An extensive DNA barcode study on Microgastrinae wasps demonstrated significant insights into their taxonomy and species discovery [22]. Such cryptic diversity has been uncovered using DNA barcodes in other animal taxa, including crustaceans, diatoms, and fish [23][24][25]. The use of DNA barcodes for the discovery of new species is emerging as a powerful tool to clarify species boundaries and to quantify species diversity [26].…”
Section: Box 1 Building the Dna Barcode Library Using Sanger Sequencingmentioning
confidence: 99%
“…DNA barcodes in conjunction with morphological, biochemical, and ecological information are revealing an outstanding diversity of species previously unrecognized through the analysis of morphological variation alone. During the first 8 months of 2014, the Web of Science recorded 310 publications in which DNA barcoding was used in discovering and describing new species, including algae [78], ferns [79], fungi [80], nematodes [81,82], arthropods [83,84], mollusks [85], fish [25], birds [86], and mammals [87]. Early on, it was expected that a single genetic marker would serve as a universal DNA barcode to identify species across the eukaryotic Tree of Life.…”
Section: Box 1 Building the Dna Barcode Library Using Sanger Sequencingmentioning
confidence: 99%
“…Initially designed to conduct individual identifications to the species level (Hubert & Hanner, ), this approach also proved to be helpful in performing a preliminary assessment of extremely diverse and poorly known fauna awaiting species delimitation (Janzen, Hajibabaei, & Burns, ; Riedel, Sagata, Suhardjono, Tänzler, & Balke, ; Smith, Fisher, & Hebert, ; Smith, Rodriguez, & Whitfield, ; Smith, Wood, Janzen, Hallwachs, & Hebert, ; Tänzler, Sagata, Surbakti, Balke, & Riedel, ). Recent large‐scale assessments of diverse ichthyofauna confirmed that the use of the cytochrome oxidase I gene successfully capture a large portion of the alpha diversity for well‐known fauna (April, Mayden, Hanner, & Bernatchez, ; Hubert, Hanner, & Holm, ; Ward, Zemlak, Innes, Last, & Hebert, ) but also helped in highlighting unrecognized (i.e., cryptic) diversity (Durand, Hubert, Shen, & Borsa, ; Hubert, Meyer, & Bruggemann, ; Jaafar, Taylor, Mohd Nor, Bruyn, & Carvalho, ; Pereira, Pazian, Hanner, Foresti, & Oliveira, ; Rock, Costa, & Walker, ; Winterbottom, Hanner, Burridge, & Zur, ). Landscape features such as fragmentation, however, proved to be a challenge to accurately delimit species through DNA barcodes (Geiger, Herder, & Monaghan, ; Keskin, Agdamar, & Tarkan, ; Knebelsberger, Dunz, Neumann, & Geiger, ).…”
Section: Introductionmentioning
confidence: 99%
“…ocean basin) to local (i.e. island) scales (Hubert et al 2012, Winterbottom et al 2014, Tornabene et al 2015. Unacknowledged cryptic diversity in Indo-West Pacific reef fish communities hampers our understanding of diversity patterns (Leprieur et al 2012, Mouillot et al 2013, Pellissier et al 2014) and their origin (McCafferty et al 2002, Kuriiwa et al 2007, Drew & Barber 2009, Leray et al 2010, Winters et al 2010, Gaither et al 2011, Borsa et al 2013, Sims et al 2014, Durand & Borsa 2015, Tornabene et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…A broad assessment of the factors promoting cryptic diversity in coral reef ecosystems is timely, because the exploration of diversity patterns in the Indo-West Pacific is an increasingly debated topic (Jokiel & Martinelli 1992, Briggs 1999, Halas & Winterbottom 2009, Hubert et al 2012, Gaither & Rocha 2013, Tornabene et al 2015. The conservation of coral reefs also requires up-todate checklists of species whose accuracy depends on the approach involved in species delineation (Hubert et al 2012, Winterbottom et al 2014, Pante et al 2015, Tornabene et al 2015.…”
Section: Introductionmentioning
confidence: 99%